Peran Pendidikan Pancasila dan Kewarganegaraan dalam Membangun Jiwa Nasionalisme Siswa SMA Muhammadiyah Mlati Sleman - Kurnia, Heri; Maya, Abu Bakar Laba; Paiman, Paiman (Academy of Social Science and Global Citizenship Journal, 2022)
The purpose of this study is to describe the extent of students' enthusiasm in building the spirit of nationalism in the family, school, and community environment. This research instills Pancasila values in students with the aim of fostering the spirit of nationalism to prevent conflicts and build good character, and be able to overcome anti-nationalism behavior in students. KDP learning needs to be recognized as teaching material that is able to protect students from anti-nationalist teachings. Pancasila values need to be lived and carried out properly, in order to become the basis and guide in acting, so that the spirit of nationalism is maintained, of course, with actions and attitudes that maintain the values of the wisdom of the Indonesian nation. The loss of the spirit of nationalism is certainly influenced by the currents of globalization that increasingly affect the mindset of students and the way of acting. This research uses descriptive qualitative methods, with data collection techniques through observation, interviews and documentation. Based on the results of the study, it can be concluded that Pancasila and Citizenship Education can build the spirit of nationalism of Muhammadiyah Mlati Sleman High School students. The spirit of student nationalism is formed through school activities, namely flag ceremonies, celebrations of the Independence Day of the Republic of Indonesia, student council activities, and scouting activities. Building the spirit of nationalism requires a lot of guidance and supervision from schools and families so that the spirit of nationalism is maintained in accordance with the values of Pancasila